Effect of 60% Shade and Trichoderma Biological Fertilizer on Vegetable Rice Gogo Growth - Sutarman; Nur Adi Santoso (Nabatia, 2021)
The aim of this study was to determine the effect of 60% shade and Trichoderma biofertilizer and its possible interaction on vegetative growth of upland rice plants up to 56 days after planting (HST) on acid soils. In this study used a split plot design that was arranged in a completely randomized design (CRD). As the main plot is a Shade consisting of no shade and shade of 60% intensity. The subplot was Trichoderma biofertilizer application consisting of without Trichoderma, Trichoderma isolate Tc-Jjr-02 and isolates Tc-Jro-01. With repeated tests 4 times were obtained 24 experimental units. The variables observed were plant height and number of tillers 7-56 HST. Observation data were analyzed using a variety analysis with a 5% test level followed by a 5% BNJ test. The results showed that there were no interaction effects between Shade and Trichoderma isolates. Each has a significant effect on the number of tillers 21-56 HST. Upland rice plants are not able to grow well under 60% shade, while Trichoderma Tc-Jro-01 isolates are the best biological agents in providing high growth responses and the number of gogopada rice tillers is sour soil.